Environmental factors that regulate Vibrio spp. abundance and community structure in tropical waters - Wong, Yi You; Lee, Choon Weng; Bong, Chui Wei; Lim, Joon Hai; Ng, Ching Ching; Kumaran, Narayanan; Edmund Sim, Ui Hang; Wang, Ai Jun (Springer Nature, 2024)
Vibrio spp. is a group of heterotrophic bacteria that are ubiquitous in marine habitats, with various ecological and clinical importance. This study investigated the environmental factors that regulate Vibrio spp. dynamics in various tropical marine habitats, including nearshore (an estuary and a coastal beach) and offshore transects located northwest and southeast of Peninsular Malaysia, while focusing on the distribution of attached and free-living Vibrio spp., population growth, and community composition. The results showed that > 85% of the Vibrio spp. in nearshore waters occurred in attached form and correlated positively to total suspended solids (TSS) and Chlorophyll a (Chla) concentrations. On the other hand, Vibrio spp. growth rates were positively correlated to dissolved organic carbon (DOC) concentrations, but negatively correlated to total bacterial counts, likely due to resource competition. In addition, high-throughput sequencing of 16S rRNA V3-V4 region showed that Vibrio spp. in these tropical waters contributed < 1 − 18% of the whole bacterioplankton community, and the six major Vibrio spp. taxa were V. alginolyticus group, V. brasiliensis, V. caribbeanicus, V. hepatarius group, V. splendidus group and V. thalassae. db-RDA (cumulative variance explicated = 93.53%) further revealed the influence of TSS, DOC, and dissolved organic nitrogen (DON) to the Vibrio spp. community profiles. The study highlighted the importance of suspended solids (TSS and Chl a) and dissolved organic nutrients (DOC and DON) towards Vibrio spp. dynamics in tropical marine waters.